Writing Ritual and the Cultural Unconscious: The Great Mother Archetype in the Composition Classroom - Cramer Cauthen (Journal of the Assembly for Expanded Perspectives on Learning, 1995)
Jungian theory and feminist epistemology can be synthesized through their mythopoetic ways of making knowledge.